Application Of Modern Informational Technologies in The Field of Education: Opportunities and Prospects (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
Informational technology plays an important role in the education system. It is known that providing access to knowledge is the role of the school, which should democratize the existing cultural heritage. In this regard, the school, thanks to informational technology, can expand the capabilities of more critical citizens who are thoughtful and ready to solve the social problems of life. Thus, informational technology brings great benefits in the aspect of education and training system. In this context, this article aims to answer: What is the importance of informational technology in education? The purpose of the study is to reflect on the importance of informational technology in the education system. Having as a bibliographic methodology based on different authors who deal with the topic being studied. The results showed that too much information supply can cause unsystematized knowledge, and the school is responsible for systematizing this knowledge. It was also concluded, that in the informational age, it is necessary to use informational technology in constructing knowledge to meet the current needs of students, in the context of technological progress.